2022
DOI: 10.1021/acsnano.1c04602
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Resolution, Dynamic Imaging of Hydrogen Absorption into Bimetallic AgPd Nanoparticles

Abstract: Palladium’s strong reactivity and absorption affinity to H2 makes it a prime material for hydrogen-based technologies. Alloying of Pd has been used to tune its mechanical stability, catalytic activity, and absorption thermodynamics. However, atomistic mechanisms of hydrogen dissociation and intercalation are informed predominantly by theoretical calculations, owing to the difficulty in imaging dynamic metal–gas interactions at the atomic scale. Here, we use in situ environmental high resolution transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Indeed, the promise for gaining this type of insight is demonstrated in a recent study of hydrogen adsorption on AgPd NPs. [ 280 ] Using ETEM, this study demonstrated the ability to track the hydrogenation‐induced lattice expansion within AgPd triangular nanoprisms. By tracking the lattice expansion in real‐time during a phase transition, surface‐limited β phase growth and rapid reorientation of the α/β interface are observed within individual particles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the promise for gaining this type of insight is demonstrated in a recent study of hydrogen adsorption on AgPd NPs. [ 280 ] Using ETEM, this study demonstrated the ability to track the hydrogenation‐induced lattice expansion within AgPd triangular nanoprisms. By tracking the lattice expansion in real‐time during a phase transition, surface‐limited β phase growth and rapid reorientation of the α/β interface are observed within individual particles.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41,42 ] When equipped with image aberration corrector and dynamic camera, the ETEM is able to achieve up to 1 Å spatial resolution and millisecond temporal resolution in an in situ experimental environment. [ 43,44 ]…”
Section: In Situ Tem Techniques For Nanocrystal Growthmentioning
confidence: 99%
“…The Ag-doped AgPd alloy nanoparticles with enhanced stability and catalytic activity were also studied by in situ ETEM to manipulate their hydrogenation process. A similar separation of α- and β-phases was observed for lightly doped (Ag concentration of ∼1%) AgPd nanoparticles at the equilibrium state, which was ascribed to the strain stabilization induced by Ag doping …”
Section: In Situ Characterization and Modulation Of Phase Transformationmentioning
confidence: 99%
“…A similar separation of αand β-phases was observed for lightly doped (Ag concentration of ∼1%) AgPd nanoparticles at the equilibrium state, which was ascribed to the strain stabilization induced by Ag doping. 404 The in situ ETEM investigation of structural and compositional restructuring in catalytically active bimetallic nano-particle systems during redox reactions has been typified by the redox-driven elemental phase segregation (atom migration between the core and the shell) in Pt−Co bimetallic nanoparticles. 405 It has been demonstrated that the different affinities between metal atoms and gas molecules can be exploited to promote the intraparticle atom migration between the surface and the core.…”
Section: In Situ Tem Gas Environment Study For Penmentioning
confidence: 99%